Impact Of Setter Training On Overhead Passing Skills Of Female Volleyball Athletes at SMK Kartek 2 Jatilawang - Vaisal Rahayu; Dian Imam Saefulah; Kusmiyati Kusmiyati; Ari Gana Yulianto; Iyan Nurdiyan Haris (PT Mediatama Zayna Indonesia, 2024)
This study aims to assess the overhead passing ability of female volleyball athletes at SMK KARTEK 2 Jatilawang after undergoing training with a setter ball. The research employs a Pre-Experimental Design using observational methods with data collection through tests. The subjects of this research are 20 female volleyball athletes. The research instrument utilized is the AAHPER to measure overhead passing ability through a Volleyball Skills Test. The data analysis technique used in this study is quantitative descriptive analysis, presented in scores adjusted according to applicable norms. The results indicate that the setter ball training shows a significant difference (0.000) in the overhead passing ability of female volleyball athletes at SMK KARTEK 2 Jatilawang.